Short-term salt stress in Brassica rapa seedlings causes alterations in auxin metabolism - Pavlović, Iva; Pěnčík, Aleš; Novák, Ondřej; Vujčić, Valerija; Radić Brkanac, Sandra; Lepeduš, Hrvoje; Strnad, Miroslav; Salopek-Sondi, Branka (Plant physiology and biochemistry, 2018)
Salinity is one of major abiotic stresses affecting Brassica crop production. Here we present investigations into the physiological, biochemical, and hormonal components of the short-term salinity stress response in Chinese cabbage seedlings, with particular emphasis on the biosynthesis and metabolism of auxin indole-3-acetic acid (IAA). Upon salinity treatments (50-200 mM NaCl) IAA level was elevated in a dose dependent manner reaching 1.6-fold increase at the most severe salt treatment in comparison to the control. IAA precursor profiling suggested that salinity activated the indole-3-acetamide and indole-3-acetaldoxime biosynthetic pathways while suppressing the indole-3-pyruvic acid pathway. Levels of the IAA catabolites 2-oxoindole-3-acetic acid and indole-3-acetic acid-aspartate increased 1.7- and 2.0-fold, respectively, under the most severe treatment, in parallel with those of IAA. Conversely, levels of the ester conjugate indole-3-acetyl-1-O-ß-d-glucose and its catabolite 2-oxoindole-3-acetyl-1-O-ß-d-glucose decreased 2.5- and 7.0-fold, respectively. The concentrations of stress hormones including jasmonic acid and jasmonoyl-isoleucine (JA and JA-Ile), salicylic acid (SA) and abscisic acid (ABA) confirmed the stress induced by salt treatment: levels of JA and JA-Ile increased strongly under the mildest treatment, ABA only increased under the most severe treatment, and SA levels decreased dose-dependently. These hormonal changes were related to the observed changes in biochemical stress markers upon salt treatments: reductions in seedling fresh weight and root growth, decreased photosynthesis rate, increased levels of reactive oxygen species, and elevated proline content and the Na+/K+ ratio. Correlations among auxin profile and biochemical stress markers were discussed based on Pearson's coefficients and principal component analysis (PCA).
Keywords: chlorid sodný; Stress, Physiological; Indoleacetic Acids; Seedlings; Auxin metabolism; semenáček; Reactive oxygen species; Principal component analysis; fyziologický stres; Brassica rapa; Growth inhibition; kyseliny indoloctové; Sodium Chloride; Short-term salinity stress; Stress hormones; Brassica rapa ssp. pekinensis